Dual‐Phase All‐Inorganic Cesium Halide Perovskites for Conducting‐Bridge Memory‐Based Artificial Synapses. (30th September 2019) - Kim, Sun Gil; Van Le, Quyet; Han, Ji Su; Kim, Hyojung; Choi, Min‐Ju; Lee, Sol A; Kim, Taemin Ludvic; Kim, Sang Bum; Kim, Soo Young; Jang, Ho Won
Abstract: Neuromorphic computing, which mimics biological neural networks, can overcome the high‐power and large‐throughput problems of current von Neumann computing. Two‐terminal memristors are regarded as promising candidates for artificial synapses, which are the fundamental functional units of neuromorphic computing systems. All‐inorganic CsPbI3 perovskite‐based memristors are feasible to use in resistive switching memory and artificial synapses due to their fast ion migration. However, the ideal perovskite phase α‐CsPbI3 is structurally unstable at ambient temperature and rapidly degrades to a non‐perovskite δ‐CsPbI3 phase. Here, dual‐phase (Cs3 Bi2 I9 )0.4 −(CsPbI3 )0.6 is successfully fabricated to achieve improved air stability and surface morphology compared to each single phase. Notably, the Ag/polymethylmethacrylate/(Cs3 Bi2 I9 )0.4 −(CsPbI3 )0.6 /Pt device exhibits non‐volatile memory functions with an endurance of ≈10 3 cycles and retention of ≈10 4 s with low operation voltages. Moreover, the device successfully emulates synaptic behavior such as long‐term potentiation/depression and spike timing/width‐dependent plasticity. This study will contribute to improving the structural and mechanical stability of all‐inorganic halide perovskites (IHPs) via the formation of dual phase. In addition, it proves the great potential of IHPs for use in low‐power non‐volatile memory devices and electronic synapses. Abstract : Neuromorphic computing, which emulates neurotransmission processes, could overcome the limitations of current von Neumann computing. In this study, a two‐terminal Ag/polymethylmethacrylate/(Cs3 Bi2 I9 )0.4 −(CsPbI3 )0.6 /Pt device successfully realizes resistive switching characteristics and synaptic behavior. The device exhibits great potential for neuromorphic computing and next‐generation non‐volatile memories. Moreover, this study will contribute to enhancing the stability of all‐inorganic halide perovskites via the formation of a dual phase.